Analisis Persepsi Keselamatan Transportasi Publik Pada Pekerja Urban di Jakarta - Cornelis Novianus; Bety Semara Lakhsmi; Awaluddin Hidayat Ramli Inaku (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Transportation safety is something that must exist in public transportation so that every worker avoids the risk of accidents during the trip. Workers' perceptions of transportation safety have an important role so that workers can understand and interpret a dangerous and risky situation as a reference in using safe public transportation. The purpose of this study was to determine the relationship between the independent variables of worker characteristics (age, gender, education), attitudes, knowledge, experience and environmental situation with the dependent variable, namely the perception of public transportation safety. This study uses descriptive and analytic methods with a Cross Sectional approach, the research instrument uses a questionnaire, the population of this study is urban workers who work in Jakarta, the research sample uses a large sample formula whose population is unknown, the population is 107 respondents, the sampling method uses non-random, purposive sampling, in this sample the urban workers who live in Bogor, Depok, Bekasi and Tangerang are taken and the statistical test uses Chi. The results of this study showed that most workers had a bad perception of public transportation safety as much as 53.3%, workers aged > 25 years as many as 61.7%, female workers 68.2%, workers with education > high school as many as 57.9 %, workers who do not have public transportation experience as much as 83.2%, workers with low knowledge as much as 53.3%, workers who have a negative attitude as much as 54.2%, and workers who experience a poor environmental situation regarding the safety of public transportation as much as 52.3%, the variables that are related in this study are the variables of attitude, knowledge, experience and environmental situation while the variables that are not related are the variables of age, gender and education, The suggestion of this research is that it is hoped that the Regional and Central Governments in organizing transportation for the public need to pay attention to adequate and quality safety facilities and provide safety driving training to drivers of public transportation.